Matharpacady-17.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Stained glass artwork on the windows at 22 Matharpacady, depicting Mother Mary and infant Jesus (on the right panel), and the Holy Communion (on the left panel). The house was donated by the Miranda family and was renamed Eymard Cottage, and opened as the Provincialate (HQ) of the SSS Order, on September 14, 2006. It has a Blessed Sacrament Chapel and offers a daily Mass for senior citizens of the gaothan.